Application of Spiral Ring Dampers in Vibration Reduction of Aeroengine Bevel Gears - Wang Yanfeng; Gao Weiqiang; Xu Yongqiang; Ou Daisong (Jixie chuandong)
In view of the problem that the vibration stress of the axle driven bevel gear of an aeroengine exceeds the permissible stress, a spiral ring friction damper is designed for the bevel gear. In detail, a concave groove is fabricated on the inside rim of gear wheels, in which the designed spiral damping ring is embedded. The circumferential deformation of the spiral damping ring is inconsistent with the gear rim under working conditions; thus the mutual friction is induced and the vibration energy could be consumed. The designed spiral damper is applied to the vibration reduction scheme of an aeroengine bevel gear. The test results show that the spiral damping ring can effectively reduce the vibration stress level of the bevel gear.The vibration reduction efficiency of the first-order, 4-pitch diameter backward traveling wave resonant vibration is about 70.7%, and that of the first-order, 3-pitch diameter forward traveling wave resonant vibration is about 53.4%. Then the vibration stress level of the gear after vibration reduction satisfies the allowable stress. Moreover, the spiral damper enjoys convenience in installation and disassembly, and possesses small additional imbalance, which leads to a promising and broad application for vibration reduction of aeroengine gears.